Psychological Analysis using Social Media Memes - Eliazer, M.; Nair, Amrutha; Saha, Disha (International Journal of Psychosocial Rehabilitation, 2020)
Nowadays what social media stands for has completely changed. Earlier, people used it to post their vacation pictures and connect with their friends. But now people are more keen on posting about their opinions, what their thoughts and emotions are, and has become their daily sources of entertainment. Social media has also led to the emergence and distribution of memes in abundance. On close inspection, a correlation can be found between the memes being created and shared by an individual and their thought and behavioral patterns. The aim of this project is to detect and analyse such a correlation using big data analytics. Large volumes of memes can be collected and classified according to their underlying sentiments using supervised machine learning algorithms. It is expected that the outcome of this project will lead to a more detailed understanding of the mindsets of the individuals sharing them and the mental or social issues they might be facing.